Protection of Citizens' Constitutional Rights in the Pancasila Democratic System in Indonesia - Amalia Geranti; H. Rusdianto; Fryanditya Rahayu Putri Rusadi (Rechtsvinding, 2026)
This study aims to analyze the protection of citizens' constitutional rights in the Pancasila democratic system in Indonesia, by highlighting the role of state institutions, the challenges faced, and the solutions that can be applied to increase their effectiveness. The research method used is normative law with a statutory and conceptual approach, which relies on an analysis of the constitution, related laws and regulations, and academic literature. Data is collected through literature studies, while data analysis is carried out through data reduction, data presentation, and conclusion drawing to produce a comprehensive picture of the implementation of the protection of citizens' constitutional rights in the context of Pancasila democracy. The results show that the protection of the constitutional rights of citizens in Indonesia has a strong foundation in the 1945 Constitution and laws and regulations, but its implementation still faces a number of challenges, including low public legal literacy, inequality in access to public services, and threats to privacy in the digital era. The role of state institutions such as the Constitutional Court, Komnas HAM, and the Ombudsman is considered significant, although it is not fully optimal due to limited resources and ineffective supervision. The proposed solutions include strengthening regulations, empowering state institutions, improving legal literacy, and using digital technology more effectively. The results of this study provide strategic recommendations to strengthen the protection of citizens' constitutional rights in the future, in accordance with the democratic values of Pancasila which emphasizes justice and common welfare.